2021
DOI: 10.1177/8755293020981995
|View full text |Cite
|
Sign up to set email alerts
|

A frequency-dependent ground-motion spatial correlation model of within-event residuals for Fourier amplitude spectra

Abstract: Ground motion time series recorded at stations separated by up to about 50 km show a frequency-dependent spatial coherency structure, and the corresponding ground motion intensity measures are found to be correlated. As omitting this correlation can result in underestimation of seismic losses in risk analysis, it is critical to quantify the spatial correlation structure for ground motion Fourier spectra estimated at different sites during a single event within a region. Toward this goal, we have developed an e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 53 publications
0
1
0
Order By: Relevance
“…They found that the cross-correlation between earthquake source parameters in the pseudo-dynamic source models significantly affects inter-frequency ground motion correlations for frequencies around 0.5 Hz, whereas the effect is not apparent at lower and higher frequencies. Furthermore, Wang et al (2019) imposed inter-period correlations on the SDSU BBP simulation methodology as a post-processing procedure and Wang et al (2021) extended this to spatial correlations.…”
Section: Validation Examples and Research Needsmentioning
confidence: 99%
“…They found that the cross-correlation between earthquake source parameters in the pseudo-dynamic source models significantly affects inter-frequency ground motion correlations for frequencies around 0.5 Hz, whereas the effect is not apparent at lower and higher frequencies. Furthermore, Wang et al (2019) imposed inter-period correlations on the SDSU BBP simulation methodology as a post-processing procedure and Wang et al (2021) extended this to spatial correlations.…”
Section: Validation Examples and Research Needsmentioning
confidence: 99%